Implications of the Transatlantic Trade and Investment Partnership (TTIP) for investment flows between the European Union and the USA - Janina Witkowska (Comparative Economic Research. Central and Eastern Europe, 2017)
The Transatlantic Trade and Investment Partnership (TTIP) is a controversial subject, but at the same time it is perceived to be the most comprehensive international agreement on free trade and investment protection. Among the topics that evoke criticism on the part of different social groups is the investor-state dispute-settlement (ISDS), as well as its legal consequences for the EU Member states. A less discussed issue is the potential implications of the agreement on the state of economic co-operation between the European Union and the USA in the field of investment flows, with special reference to foreign direct investment (FDI). The aim of this paper is to present the discussion related to the ISDS and examine some of the economic, political and legal implications of TTIP provisions for FDI flows between the EU and the USA. The proposals of the European Commission to change the investment protection system might be treated as an attempt to make the system of arbitrage more transparent and convincing to societies, and safer for states. The effects of the TTIP agreement for FDI between both partners might be dependent on the scale of trade creation and diversion effects, and the mirror effects of investment creation and diversion under a free trade area.
Keywords: F21; 330; Transatlantic Trade and Investment Partnership (TTIP); investor-state dispute-settlement (ISDS); foreign direct investment (FDI); USA; UE